Near‐surface strong winds in a marine extratropical cyclone: acceleration of the winds and the importance of surface fluxes. (13th November 2016) - Slater, Tim P.; Schultz, David M.; Vaughan, Geraint
Abstract : A rapidly developing extratropical cyclone named Tini brought strong winds to Ireland and the United Kingdom on 12 February 2014. A mesoscale‐model simulation is used to analyze the development of the strong winds through the terms in the horizontal momentum equation. The maximum of near‐surface wind speed equatorward of the cyclone was composed of two different airstreams that underwent different paths to acceleration. First, horizontally moving air in the cold conveyor belt was accelerated by the along‐flow pressure gradient force but was decelerated by friction. Second, descending air accelerated into the eastern end of the maximum of near‐surface wind speed and was associated, in part, with a sting jet, caused by the increasing along‐flow horizontal pressure gradient force at lower levels. When this descending air entered the boundary layer, it too was decelerated by surface friction. Surface fluxes of heat and moisture were necessary to destabilize and deepen the boundary layer, allowing mixing of the strongest winds from the free troposphere down to the surface. A simulation with the surface fluxes turned off during cyclogenesis showed a more stable boundary layer around the bent‐back front, which inhibited the strongest winds from reaching the surface. The descent of the sting‐jet air was associated with a maximum in quasigeostrophic omega, which consisted of both synoptic‐scale and mesoscale descent, the latter associated with frontolysis occurring at the end of the bent‐back front. Thus, the near‐surface wind maximum was created by the synoptic‐scale and mesoscale dynamics, whereas localized moist processes were negligible.